Persepsi Guru Paud Tentang Media Pembelajaran Berbasis Multimedia Interaktif - Rici Oktari; Despa Ayuni (Journal on Education, 2024)
A teacher certainly has an important role in the teaching and learning process, the teacher's perception in using interactive multimedia-based learning media is a very important thing to know in order to increase creativity and innovation in the teaching and learning process in the current digital era. The aim of this research is to determine teachers' perceptions about interactive multimedia-based learning media in PAUD Pino District, South Bengkulu Regency. The type of research in this research is qualitative research. This research uses a purposive sampling technique using data collection techniques in the form of interviews and observations. The analysis technique in this research consists of data collection, data reduction, data presentation, and drawing conclusions. With the following research results: Teachers in Pino District, South Bengkulu Regency realize the importance of using interactive multimedia-based learning media in this era of globalization. The use of interactive multimedia-based learning media, as much as 80% was obtained from the internet, friends and the YouTube application and as much as 20% was obtained by how to make it yourself autodidactically. Early use of interactive multimedia-based learning media certainly pays attention to the objectives and material to be conveyed by paying attention to the technical quality of the learning media such as image or video quality, sound quality, suitability of the sound to the duration of the video, suitability of the text, and suitability of the music used. Interactive multimedia-based learning media in terms of meeting all the needs of children's characteristics is very difficult to do, so consideration of children's characteristics in using learning media needs to be done in order to achieve learning objectives. Teachers realize that interactive multimedia-based learning media has weaknesses and advantages, so that teachers and researchers obtain solutions to the problems of using interactive multimedia-based learning media that have been used in PAUD.